1985
DOI: 10.1177/002076408503100402
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Psychopathology between Black and White Schizophrenics

Abstract: The psychopathology of black and white schizophrenics was compared in 275 consecutive admissions of schizophrenics, who were rated on two rating scales by psychiatrists, using a structured interview. There were significant differences between black and white schizophrenics; blacks exhibited more frequent symptoms of angry outbursts, poor communication, disorientation, asocial behaviour and auditory and visual hallucinations, while whites showed more frequent symptoms of unsystematized delusions. When controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Previous investigators have shown that besides misdiagnosis of the AfricanAmerican patient, African-Americans are more likely to receive antipsychotic medications when they are not needed (Adebimpe, 1981;Chu et al, 1985;Flint, 1991). Additionally, African-Americans are more likely than Caucasians to receive asneeded (PRN) medication and higher doses of antipsychotics (Flaherty and Meagher, 1980;Strickland et al, 1991;Adebimpe, 1981;Chu et al, 1985;Flint, 1991). However, in this study, no signi®cant dierences were found in the type, dose of medication or side-eect pro®le between African-Americans and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have shown that besides misdiagnosis of the AfricanAmerican patient, African-Americans are more likely to receive antipsychotic medications when they are not needed (Adebimpe, 1981;Chu et al, 1985;Flint, 1991). Additionally, African-Americans are more likely than Caucasians to receive asneeded (PRN) medication and higher doses of antipsychotics (Flaherty and Meagher, 1980;Strickland et al, 1991;Adebimpe, 1981;Chu et al, 1985;Flint, 1991). However, in this study, no signi®cant dierences were found in the type, dose of medication or side-eect pro®le between African-Americans and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that African-Americans are more likely than Caucasians to be diagnosed with schizophrenia (Schoenberg et al, 1985;Jones and Gray, 1986;Fabrega et al, 1988;Adebimpe, 1981;Lawson et al, 1994;Strakowski et al, 1995) and consequently are more likely to be treated with antipsychotic medications (Chu et al, 1985) (see Table 2). A higher prevalence of hallucinations and delusions among African-American patients with schizophrenia (Heyman et al, 1991;Schoenberg et al, 1985;Jones and Gray, 1986;Fabrega et al, 1988;Adebimpe, 1981;Lawson et al, 1994;Strakowski et al, 1995;Chu et al, 1985) and mood disorder (Jones and Gray, 1986) has been reported. In a review of the literature, Flint (1991) reported a prevalence of delusional symptoms ranging from 15% to 56% in patients with Alzheimer's disease and from 27% to 60% in patients with vascular dementia.…”
mentioning
confidence: 99%
“…The expression of psychosis may vary with cultural background (Adebimpe et al, 1981, Arnold et al, 2004, 8 Barrio et al, 2003, Bauer et al, 2011, Chang et al, 2011, Chu et al, 1985, Littlewood and Lipsedge, 1981, 9 Maslowski et al, 1998, Radhakrishnan et al, 1983, Suhail and Cochrane, 2002, Thomas et al, 2007, Weisman 10 et al, 2000, Yamada et al, 2006. There may be cultural differences in the content of psychotic symptoms 11 (Maslowski et al, 1998, Viswanath and Chaturvedi, 2012, Weisman et al, 2000, Yamada et al, 2006 and/or 12 in the language with which these symptoms are expressed (Kleinman, 1987).…”
mentioning
confidence: 99%
“…White patients with schizophrenia have been found to display more grandiosity in their delusional content and more severe excitement symptom scores than their Black counterparts, as measured by the Positive and Negative Symptom Scale (PANSS) (Barrio et al, 2003). Chu and colleagues (1985) reported that Black patients with schizophrenia showed more anger, disorientation, asocial behavior, and hallucinations, whereas White patients exhibited more symptoms of irrelevant speech. White patients have been reported to be more symptomatically impaired and show more emotional disturbance, behavioral problems, negative symptoms, and flat affect than their Black counterparts (Barrio et al, 2003; Fabrega, Mezzich, & Ulrich, 1988).…”
mentioning
confidence: 99%